Phenetic analysis of Curcuma spp. in Yogyakarta, Indonesia based on morphological and anatomical characters - Mulya Sungkawati; L. HIDAYATI; B.S. DARYONO; Purnomo Purnomo (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sungkawati M, Hidayati L, Daryono BS, Purnomo. 2019. Phenetic analysis of Curcuma spp. in Yogyakarta, Indonesia based on morphological and anatomical characters. Biodiversitas 20: 2340-2347. Curcuma spp., also known as ginger (Zingiberaceae), has economic value in traditional medicine. However, its many morphological variations cause difficulties in identification and classification. Therefore, observation of its morphological and anatomical characteristics, and of the phenetic relationships between Curcuma species, is important. This research aims to determine the specific characteristics of Curcuma spp. and to examine its phenetic relationships based on morphological and anatomical characteristics. The research was conducted in July 2018-February 2019 in the Bantul, Gunungkidul, Sleman and Karanganyar regions. Observation of the anatomical characteristics was conducted on the leaves and rhizomes and the data analyzed according to descriptive and quantitative/numerical methods. Clustering analysis with the Gower General Similarity Coefficient and Principal Component Analysis (PCA) was performed to determine the role of each character in groupings. The results of the research found seven species from 23 OTUs observed (C. aeruginosa, C. domestica, C. manga and C. xanthorrhiza, each with four OTUs; C. soloensis and C. zedoaria, with three OTUs each; and C. heyneana with one OTU) and showed that specific morphological characteristics were found in the flesh color rhizome, pseudostem color and midrib color. Specific anatomical characteristics were evident in the secretion cell color and the presence of trichomes on the leaves and rhizomes. The dendrogram shows a 0.70 phenon line consisting of two groups, group A (C. soloensis and C. domestica) fused in a 0.760 similarity index, and group B (C. aeruginosa, C. mangga, C. heyneana, C. soloensis, C. xanthorrhiza and C. zedoaria) fused in a 0.654 similarity index, which means that C. soloensis and C. domestica have a close phenetic relationship. The 0.80 phenon line consisted of five groups: C. domestica, C. soloensis, C. xanthorrhiza, C. zedoaria-C. mangga-C. heyneana and C. aeruginosa.